2000
DOI: 10.1093/her/15.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Are tailored health education materials always more effective than non-tailored materials?

Abstract: While promising, the evidence in support of tailored health communication has not been overwhelming. One explanation is that tailored materials may be far superior to non-tailored materials in some cases, but only slightly better, no different or less effective in others. In this study, 198 overweight adults were randomly assigned to receive either tailored or non-tailored weight loss materials. Participants' cognitive, affective and behavioral responses to the materials were measured at an immediate and 1 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
183
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(192 citation statements)
references
References 24 publications
6
183
0
3
Order By: Relevance
“…This result coincided with the findings of Doshi et al (2003), who concluded that online physical activity websites provided adequate knowledge-based information and guidelines, but incorporated very few theory-based strategies [14]. This and other research has concluded that there is a need for websites to improve interaction and to better tailor assistance to the needs of users, since these methods are expected to have greater impact on behavior change [20]. This is consistent with the traditional approach of health education that largely focuses on the dissemination of health information.…”
Section: Discussionsupporting
confidence: 82%
“…This result coincided with the findings of Doshi et al (2003), who concluded that online physical activity websites provided adequate knowledge-based information and guidelines, but incorporated very few theory-based strategies [14]. This and other research has concluded that there is a need for websites to improve interaction and to better tailor assistance to the needs of users, since these methods are expected to have greater impact on behavior change [20]. This is consistent with the traditional approach of health education that largely focuses on the dissemination of health information.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, we refer to "mode tailoring" as adjusting information to match individual preferences for presentation modality, using verbal (text), visual (static illustrations), and/or audiovisual (videos) information (Mayer, 2001). Mode tailoring is important, as the way in which message content is processed and remembered very much depends on how this information is being delivered (Kreuter, Oswald, Bull, & Clark, 2000;Ritterband, Thorndike, Cox, Kovatchev, & Gonder-Frederick, 2009). The ability to correctly remember and reproduce information is often referred to as recall of information (Jansen et al, 2008;Lang, 2000).…”
Section: Mode-tailored Online Informationmentioning
confidence: 99%
“…However, it is more typically the case that a clinical population varies considerably in terms of behavior, motivation, learning needs, and other characteristics. In such cases, tailored educational materials often prove to be more effective than generic media [38][39][40]. Tailored messages are those that are individually customized and can, for example, address a person's particular diagnostic, motivational, or behavioral characteristics.…”
Section: Introductionmentioning
confidence: 99%